AB0421 Outcomes of infliximab treatment in canadian rheumatoid arthritis patients of different age groups. (23rd January 2014) - Faraawi, R.; Baker, M.; Bensen, W.; Rampakakis, E.; Sampalis, J.; Otawa, S.
Abstract : Objectives: Rheumatoid Arthritis (RA) is a chronic inflammatory disease with an average age of onset of ∼55 years. Given that aging affects many biological processes, including immunological, the patient profile and response to anti-TNF treatment may differ with age. The objective of this real-life observational Canadian study was to assess the influence of age on baseline characteristics as well as on response to treatment with Infliximab. Methods: Data for this analysis were obtained from BioTRAC, an observational prospective registry of adult RA patients initiated on treatment with Infliximab since 2002 and managed as per routine care. Patients enrolled were biologic-naïve or had initiated treatment with a biologic for a period of <6 months prior to enrolment. In this analysis, 545 RA patients were included who were enrolled by June, 2011 and had at least one follow-up assessment. Patients were divided into 5 subgroups based on age at time of enrollment: ≤40, 41-50, 51-60, 61-70, and >70 years. Results: Among the 545 patients comprising the study cohort, 14% were ≤40 years of age, 18% were 41-50 years-old, 31% were 61-70 years of age, while 23%, and 14% of patients belonged to the 61-70, >70 age subgroups, respectively. At baseline, a significantly higher proportion in the older subgroups were RF+ (60%, 68%, 79%, 77%, and 79% of patients, respectively) and of female gender (74%, 69%, 71%, 83%, 84% of patients, respectively). Furthermore, significant between-group differences were observed in disease duration (P<0.001), HAQ (P<0.001), ESR (P<0.001), CRP (P=0.021), and DAS28-ESR (P=0.003) with disease duration and severity increasing with age. However, morning stiffness, TJC, SJC, SGA, PGA and DAS28-CRP were comparable between-groups. Upon 6-months of treatment, remission achievement was significantly higher in younger subgroups with 41%/27%/15%/17%/13% of patients achieving DAS28-ESR remission, 31%/36%/16%/17%/17% achieving DAS28-CRP remission, 20%/27%/5.4%/11%/13% achieving SDAI remission, and 15%/13%/4%/6%/5% of patients achieving ACR/EULAR remission in the ≤40, 41-50, 51-60, 61-70, and >70 patient subgroups, respectively. However, regardless of age group, all parameters studied (morning stiffness, HAQ, ESR, CRP, TJC, SJC, SGA, PGA, SDAI, DAS28-ESR, and DAS28-CRP) significantly (P<0.05) improved over time upon treatment with Infliximab for 36-months, with the exception of ESR in the >70 years-of-age subgroup. Conclusions: The results of this observational study have shown that Infliximab is effective in improving outcomes in rheumatoid arthritis over a three year period, regardless of age. However, significant variation in patient baseline characteristics and remission rates within various age groups is observed. Disclosure of Interest: None Declared